2021
DOI: 10.3390/plants10091844
|View full text |Cite
|
Sign up to set email alerts
|

Identification and First Report of Fusarium andiyazi Causing Sheath Rot of Zizania latifolia in China

Abstract: Zizania latifolia is a perennial plant native to East Asia. The swollen culm of Z. latifolia is a popular vegetable and traditional herbal medicine consumed in China and some other Asian countries. From 2019 to 2021, a sheath rot disease was found in Zhejiang Province of China. Symptoms mainly occurred in the leaf sheath showing as brown necrotic lesions surrounded by yellow halos. The pathogen fungal isolates were isolated from the affected sheaths. Ten representative isolates were selected for morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In the case of our study, the TEF1 and RPB2 sequences proved to be sufficient for the unambiguous assignment of the nineteen isolates to four Fusarium species. Many recent studies have used the same two regions for Fusarium species identification [ 7 , 8 , 38 , 39 , 40 , 41 , 42 , 43 ]. Our research has confirmed that sequencing is essential for distinguishing Fusarium species.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of our study, the TEF1 and RPB2 sequences proved to be sufficient for the unambiguous assignment of the nineteen isolates to four Fusarium species. Many recent studies have used the same two regions for Fusarium species identification [ 7 , 8 , 38 , 39 , 40 , 41 , 42 , 43 ]. Our research has confirmed that sequencing is essential for distinguishing Fusarium species.…”
Section: Discussionmentioning
confidence: 99%